2020
DOI: 10.3390/f11020248
|View full text |Cite
|
Sign up to set email alerts
|

Rural Household Livelihood and Tree Plantation Dependence in the Central Mountainous Region of Hainan Island, China: Implications for Poverty Alleviation

Abstract: Plantations support local economies and rural livelihoods in many mountainous regions, where poverty and a fragile environment are often interlinked. Managing plantations sustainably and alleviating poverty is a major challenge. This study reports on the findings of a household livelihood survey in the central mountainous region of Hainan Island, a global biodiversity hotspot. The survey aimed to identify rural household livelihoods, strategies to lift rural households out of poverty and potential environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Therefore, improved incomes of rural households enable better access to education for children and youths in rural areas. This, in turn, will contribute to further social and economic development [13].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, improved incomes of rural households enable better access to education for children and youths in rural areas. This, in turn, will contribute to further social and economic development [13].…”
Section: Introductionmentioning
confidence: 98%
“…The extensive agricultural land in rural areas was well utilized by tappers. Li et al (2020) in his research found that agricultural land was the most important natural capital for villagers, so that extensive land ownership will increase household income significantly.…”
Section: Natural Capitalmentioning
confidence: 99%
“…Najera introduced the multidimensional poverty index (MPI), a measure of severe poverty, which was understood as the inability of a person to meet minimum international standards in terms of indicators related to the millennium development goals and core functions. This was the first time that more than 100 developing countries had implemented direct measures of poverty [15]. Yongbin et al proposed a new multidimensional poverty index (MPI-LA).…”
Section: Literature Reviewmentioning
confidence: 99%